Trajnostni razvoj mest in naravne nesreče - Ciglič, Rok; Komac, Blaž; Tičar, Jure; Zorn, Matija (Naravne nesreče, 2017)
The volume ('Sustainable Urban Development and Natural Disasters') contains seventeen chapters dealing with natural disasters. The chapters describe research findings and examples of the use of modern technologies in cases of natural disasters, with the focus on natural disasters in urban areas. The volume covers various topics such as earthquakes, floods, avalanches, landslides, heat waves, urban heat island, and web applications.